Hubungan Sanitasi Lingkungan dan PHBS dengan Stunting pada Balita Usia 0-59 Bulan di Dusun Sembilang - Jayanti, Jahia; Flora, Rostika (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: Stunting is a problem that occurs in low and middle-income countries including Indonesia, especially in rural areas. Stunting has a detrimental functional effect on child growth and development. Some indirect causes of stunting include environmental sanitation and clean and healthy living behavior. This study aims to determine the relationship between environmental sanitation and clean and healthy living behavior with stunting in toddlers aged 0-59 months.. Methods: This was a quantitative study with a cross-sectional research design. The population of this study involved toddlers aged 0 to 59 months with sample of 50 toddlers, the sampling technique used being a purposive sampling according to the inclusion criteria. The research instruments for environmental sanitation and clean and healthy living behavior were measured through a questionnaire. The stunting variable was measured directly using a infantometer and stadiometer. Data analysis used univariate and bivariate analysis using the Chi-Square test. Results: There is no significant relationship between environmental sanitation with stunting (p=1.000). There is a significant relationship between clean and healthy living behavior with stunting (p=0.005). Conclusion: Clean and healthy living behavior plays an important role in the incidence of stunting in toddlers aged 0–59 months, while environmental sanitation does not show a significant relationship. Education is needed regarding increasing clean and healthy living behavior in an effort to reduce the prevalence of stunting.